Supporting a systems approach to scaling for all; insights from using the Scaling Scan tool - Woltering, Lennart; Valencia Leñero, Eva M.; Boa, Maria; Van Loon, Jelle; Ubels, Jan; Leeuwis, Cees (Elsevier, 2024)
CONTEXT: Approaches to scaling are persistently linear and focus on a single innovation, an innovator to control the scaling process, and a purpose driven by donor accountability. Alternative approaches that better reflect the complexity involved in sustainable development draw on systems thinking theory, but are hardly used. The Scaling Scan tool facilitates the integration of a systems approach to scaling to a broad public.